Octreotide Use in a Patient with MEN-1 Syndrome and Multifocal Pancreatic Neuroendocrine Tumors: A Case Report and Review of the Literature - Matthew H. Kemm (Case Reports in Gastrointestinal Medicine, 2019)
We report a patient with multiple endocrine neoplasia type 1 with pancreatic polypeptide (PP) secreting subcentimeter pancreatic neuroendocrine tumors (pNETs) treated with octreotide and review the current literature that pertains to the management of these patients. Clinical data, laboratory results, and imaging were reviewed. A literature search was performed in PUBMED using combinations of the terms “multiple endocrine neoplasia type 1,” “somatostatin,” octreotide,” “pancreatic polypeptide,” and “pancreatic tumor.” Relevant references were selected and reviewed. A 43-year-old male with a history of MEN1 and multiple subcentimeter neuroendocrine tumors with elevation of PP was treated with octreotide therapy leading to a reduction and normalization of PP levels. The patient tolerated octreotide therapy but self-discontinued octreotide after 24 months with a rise in PP levels off therapy. Tumors remained stable in size through 40 months of imaging follow-up. In patients with MEN1 and subcentimeter pNETs, octreotide therapy is well tolerated and can lead to a significant drop in PP levels with no change in lesion size. There is insufficient data to suggest long-term benefit with octreotide therapy but it may be considered versus standard conservative management.